Suicide among those who use mental health services: Suicide risk factors as evidenced from contact-based characteristics in Victoria - Fernando, Tharanga; Clapperton, Angela; Spittal, Matthew; Berecki-Gisolf, Janneke (Frontiers in Psychiatry, 2022)
Objective The majority of suicide decedents have had contact with health services in the months before their death. Contacts for mental health services present potential suicide prevention opportunities. This study aims to compare contact-based characteristics among suicide decedents and living controls in the year subsequent to clinical mental health contact with the public health system in Victoria, Australia. Methods A population-based nested case-control study of those who had mental health-related hospital and community contacts with the public health system was conducted. Cases (suicide decedents) were age and gender-matched to living controls (suicide non-decedents). These records were linked to records of suicides that occurred in the 12 months following the health service contact, between January 1, 2011, and December 31, 2016. Victorian residents aged 10 years and above were selected at the time of contact (483,933 clients). In the study population, conditional logistic regression models were used to assess the relationship between contact-based characteristics and suicide. Socio-demographics and mental health-related hospital and community contact data was retrieved from the Victorian Admitted Episodes Dataset, the Victorian Emergency Minimum Dataset and the Public Clinical Mental Health database and suicide data from the Victorian Suicide Register. Results During a six-year period, 1,091 suicide decedents had at least one mental health contact with the public health system in the 12 months preceding the suicide. Overall, controls used more mental health services than cases; however, cases used more mental health services near the event. The relationship between the type of service and suicide differed by service type: hospital admissions and emergency department presentations had a significant positive association with suicide with an OR of 2.09 (95% CI 1.82–2.40) and OR of 1.13 (95% CI 1.05–1.22), and the effect size increased as the event approached, whereas community contacts had a significant negative association with an OR of 0.93 (95% CI 0.92–0.94), this negative association diminished in magnitude as the event approached (OR∼1). Conclusion Suicide decedents had less contact with mental health services than non-decedents; however, evidence suggests suicide decedents reach out to mental health services proximal to suicide. An increase in mental health service contact by an individual could be an indication of suicide risk and therefore an opportunity for intervention. Further, community level contact should be further explored as a possible prevention mechanism considering the majority of suicide decedents do not access the public clinical mental health services.